(untitled) (Sudurpaschim Spectrum, 2024)
This paper focuses on assessing Nepalese women’s decision-making power and accepting partner violence based on the conduct undercover on the 2022 Nepal DHS. The female subjects include 14,845 women from a selected household through a multistage random sampling procedure throughout the country, and after various data cleansing of the overall study sample 4211 was selected. Cross-tabulation and multivariate logistic regression analyses were used to test the bivariate association of women’s autonomy on the acceptability of DWB controlling for Age, Education, Wealth, Ethnicity and Region. From these works, it is clear that young women between the ages of 15-24 have low decision-making power when extended with education and wealth in a household. With regards to ethnic groups and regions, Brahmin/Chhetri women reported the highest decision-making power (Bagmati province) and Dalit women and Karnali province had the lowest ethnic group and regional decision-making power. As with the case of attitudes toward acceptance of divorce, the socio-economic variables affected approval of domestic violence but the female respondents under 35 years of age and those who had education did not approve of wife beating. Hence the study suggests that if exist educational attainment, income and spatial disparities could raise the status of women and reduce the patience that Nepali society has with this violence.